Stand density management diagrams of Eucalyptus Viminalis: predicting stem volume, biomass and canopy cover for different production purposes - Gyenge, Javier (2019)
Stand density management diagrams (SDMD) provide a guide for forest density management taking into account stands attributes such as trees´ diameter or volume. One of the most common species planted in Pampean plains of Argentina is Eucalyptus viminalis for multiple objectives: solid wood use or firewood in local markets, pulp for cellulose industry and to provide services for agriculture and cattle raising (windbreaks or cattle refuge). The objective of this study was to gather the available production information /inventory data and to develop a first SDMD for estimating standing volume, biomass and canopy cover of E. viminalis as a tool for forest managers aiming at different plantation purposes. Data to develop the SDMD were obtained from 161 plots, distributed along a climate and soil gradient. We also generated two predictive equations capable of estimating dominant height from the diameter of the trees as well as canopy cover from stand basal area. As an example of application, the SDMD was used to estimate the wood production of three alternative systems: a) an unmanaged plantation (simulating a common practice in the region), b) a mixed production system such as an agroforestry system, and c) a plantation that maximizes wood biomass or volume production.